Does a Large Ear Type Wheat Variety Benefit More From Elevated CO2 Than That From Small Multiple Ear-Type in the Quantum Efficiency of PSII Photochemistry? - Li, Yuting; Li, Xin; Li, Yujie; Zhuang, Shu; Feng, Yongxiang; Lin, Erda; Han, Xue (Frontiers in Plant Science, 2021)
Recently, several reports have suggested that the growth and grain yield of wheat are significantly influenced by high atmospheric carbon dioxide concentration (CO2) because of it photosynthesis enhancing effects. Moreover, it has been proposed that plants with large carbon sink size will benefit more from CO2 enrichment than those with small carbon sink size. However, this hypothesis is yet to be test in winter wheat plant. Therefore, the aim of this study was to examine the effect of elevated CO2 (eCO2) conditions on the quantum efficiency of photosystem II (PSII) photochemistry in large ear-type (cv. Shanhan 8675; greater ear C sink strength) and small multiple ear-type (cv. Early premium; greater vegetative C source strength) winter wheat varieties. The experiment was conducted in a free air CO2 enrichment (FACE) facility, and three de-excitation pathways of the primary reaction of PSII of flag leaf at the anthesis stage were evaluated under two CO2 concentrations (ambient [CO2], ~415 µmol·mol-1, elevated [CO2], ~550 µmol·mol-1) using a non-destructive technique of modulated chlorophyll fluorescence. Additionally, the grain yield of the two varieties was determined at maturity. Although elevated CO2 increased the quantum efficiency of PSII photochemistry (ΦPSII) of Shanhan 8675 (SH8675) flag leaves at the anthesis stage, the grain number per ear and 1000-kernel weight were not significantly affected. In contrast, the ΦPSII of early premium (ZYM) flag leaves was significantly lower than that of SH8675 flag leaves at the anthesis stage, which was caused by an increase in the regulatory non-photochemical energy dissipation quantum (ΦNPQ) of PSII, suggesting that light energy absorbed by PSII in ZYM flag leaf was largely dissipated as thermal energy. The findings of our study showed that although SH8675 flag leaves exhibited higher C sink strength and quantum efficiency of PSII photochemistry at the anthesis stage, these factors alone do not ensure improved grain yield under eCO2 conditions.